CDK4/6 inhibitors in breast cancer – from in vitro models to clinical trials. (1st February 2020) - Saleh, Lubaid; Wilson, Caroline; Holen, Ingunn
Abstract: Background: Breast cancer (BC) is one of the leading causes of cancer-related deaths worldwide. Standard therapies aim to disrupt pathways that regulate the growth and survival of BC cells. Therapeutic agents such as endocrine therapy target hormone dependent cancer cells and have shown to be suitable approaches in BC treatment. However, in the case of metastatic BC, curative options are limited, thus strategies have been explored to improve survival and clinical benefit. In this review we provide an up to date overview of the development of anti-cancer agents, particularly the newly developed CDK4/6 inhibitors. Material and methods: A search of PubMed was conducted to identify preclinical data surrounding the development of endocrine therapy and CDK4/6 inhibitors in early and metastatic BC. Clinical data were also sought using PubMed and clinicaltrials.gov. Results: Agents targeting oestrogen and its receptor have demonstrated positive outcomes in clinical trial with improvements in objective responses and overall survival. However, patients do exhibit adverse effects and some will eventually fail to respond to endocrine therapy. Subsequently, the development and success of 3rd generation CDK4/6 inhibitors in preclinical studies has allowed their introduction in clinical studies. In patients with ER + BC, CDK4/6 have demonstrated dramatic improvements in progression free survival when used in combination with endocrine therapies. Similar findings were also observed in metastatic disease. Adverse effects were limited in CDK4/6 treated patients, demonstrating the safety of these agents. Conclusion: CDK4/6 inhibitors are highly specific making them a safe and viable therapeutic for BC and there is increasing evidence of their potential to improve survival, even in the metastatic setting. Although a number of trials have demonstrated this, as a lone therapy or in combination, optimisation of treatment scheduling are still required in further clinical investigations.